Factors influencing purchase intention behaviour among female young generation on halal collagen beauty drinks / Ainol Asyikin Annuar - Annuar, Ainol Asyikin (Faculty of Business and Management, 2015)
The primary attempt in this study is to examine the factors influencing female purchase intention on halal collagen beauty drinks at Tampin, Negeri Sembilan. This study explores the relationship between three factors which consist of attitude, subjective norms and knowledge that could influence female purchase intention on halal collagen beauty drinks. This study also tries to find out the most factors that influencing female purchase intention on halal collagen beauty drinks at Tampin.